Short-term rapamycin treatment increases life span and attenuates aortic aneurysm in a murine model of Marfan-Syndrome - Zaradzki, Marcin; Rehberg, Franziska; Lont, Sebastian Alexander; Soethoff, Jasmin; Remes, A.; Arif, Rawa; Müller, Oliver J.; Karck, Matthias; Hecker, Markus; Wagner, Andreas H. (Biochemical pharmacology, 2022)
Background - Marfan syndrome (MFS) is a genetic disorder leading to medial aortic degeneration and life-limiting dissections. To date, there is no causal prevention or therapy. Rapamycin is a potent and selective inhibitor of the mechanistic target of rapamycin (mTOR) protein kinase, regulating cell growth and metabolism. The mgR/mgR mice represent an accepted MFS model for studying aortic pathologies to understand the underlying molecular pathomechanisms. This study investigated whether rapamycin inhibits the development of thoracic aortic aneurysms and dissections in mgR/mgR mice. - Methods - Isolated primary aortic smooth muscle cells (mAoSMCs) from mgR/mgR mice were used for in vitro studies. Two mg kg/BW rapamycin was injected intraperitoneally daily for two weeks, beginning at 7-8 weeks of age. Mice were sacrificed 30 days post-treatment. Histopathological and immunofluorescence analyses were performed using adequate tissue specimens and techniques. Animal survival was evaluated accompanied by periodic echocardiographic examinations of the aorta. - Results - The protein level of the phosphorylated ribosomal protein S6 (p-RPS6), a downstream target of mTOR, was significantly increased in the aortic tissue of mgR/mgR mice. In mAoSMCs isolated from these animals, expression of mTOR, p-RPS6, tumour necrosis factor α, matrix metalloproteinase-2 and -9 was significantly suppressed by rapamycin, demonstrating its anti-inflammatory capacity. Short-term rapamycin treatment of Marfan mice was associated with delayed aneurysm formation, medial aortic elastolysis and improved survival. - Conclusions - Short-term rapamycin-mediated mTOR inhibition significantly reduces aortic aneurysm formation and thus increases survival in mgR/mgR mice. Our results may offer the first causal treatment option to prevent aortic complications in MFS patients.
Online verfügbar 2 Oktober 2022, Artikelversion 6 Oktober 2022
Gesehen am 17.01.2023